The Impact of the Irrelevant: Temporary Buy-Options and Bidding Behavior in Auctions - Ronald Peeters; Martin Strobel; Dries Vermeulen; Markus Walzl (Games, 2016)
With a laboratory experiment, we study the impact of buy-options and the corresponding buy-price on revenues and bidding behavior in (online) proxy-auctions with independent private valuations. We show that temporary buy-options may reduce revenues for two reasons: At low buy-prices, the application of the buy-option avoids revenue-enhancing bidding; at high buy-prices, bidders are reluctant to bid above the option price (even though the option is no longer available once an auction has started). The latter suggests a particular type of anchoring, where bidders use the buy-price to update their expectations about the strengths of their opponents.